Heros Dew Drop Series: Sir Ahmadu Bello - Ugwunebo, Chukwuike and Nnaji, Vera Scot (Heros Dew Drops Ltd, 2013)
This book contains the stories of Nigeria Hero (Sir Ahmadu Bello) retold in lucid language and replete with colourful pictures. The beauty of the story lies in the way the virtues of our heroes are laid out to inspire and encourage the young ones.
Keywords: Biography & Autobiography; Juvenile Non-Fiction; Sir Ahmadu Bello